Effective performance appraisals - Maddux, Robert B. (Crisp Pub. Menlo ParkUS, 1993)
Instructs managers about creating a working environment that would make effective performance appraisals possible. Teaches them how to prepare for and conduct performance appraisal meetings and the necessary follow-up.